herman de vries, random objectivation v67-36c - Cees de Boer; Rob de Windt (The Rijksmuseum Bulletin)
In its collection of twentieth-century art, the Rijksmuseum holds several works by the artist herman de vries. Among them is an exceptional white wall relief from 1967 measuring more than six metres across, on long-term loan from Wageningen University & Research random objectivation v67-36c was created as an art commission for the then newly built accommodation of the Instituut voor Toegepast Biologisch Onderzoek in de Natuur (ITBON), where de vries was working as a research assistant at the time. The relief belongs to an extensive series of artworks de vries called random objectivations, conceived on the basis of mathematical tables of objective-random numbers used by de vries in conducting biological experiments and subsequent evaluations. As revealed by the authors’ research in the ITBON archives, the nature of de vries’s scientific activities during these years centred on the study of ecological networks, an approach first developed in the late nineteen twenties as a new paradigm in the field of biology. By examining the scientific context in which de vries’s relief was created, the authors arrive at a more focused interpretation and ecological contextualization of de vries’s random objectivations.